Implementation of Digital Culture in Improving the Quality and Competitiveness of Education at State Senior High School 1 Lhokseumawe - Putri Syawalina; Muhammad Ilham (Pusdikra Publishing, 2026)
The implementation of digital culture in educational institutions is becoming increasingly important amidst the rapid development of information and communication technology. This study aims to examine how digital culture is implemented to improve the quality and competitiveness of education at SMA Negeri 1 Lhokseumawe. A descriptive qualitative approach was used through field observations, in-depth interviews with school stakeholders, and analysis of institutional documents. The results show that digital culture at SMA Negeri 1 Lhokseumawe is systematically implemented through four main programs: digital technology training, school website management, Canva-based graphic design training, and Microsoft Excel spreadsheet training. These programs are designed for teachers, administrative staff, and students to strengthen their digital competencies and support more effective educational practices. The principal's visionary leadership plays a central role as the main driver behind the school's digital transformation. However, the implementation process still faces several challenges, including differences in digital literacy levels among school members, limited network infrastructure, and the potential risk of moral degradation due to uncontrolled technology use. To overcome these obstacles, the school implemented several strategic efforts, such as holding biweekly Focus Group Discussions (FGDs), providing intensive mentoring, and actively involving parents in supervising students' technology use. The study concluded that the implementation of digital culture has made a significant contribution in improving the quality of teaching and learning, increasing teacher job satisfaction, improving administrative efficiency, and strengthening the school's reputation and overall competitiveness in the education sector.